Violence against Women: Legal, Neuropsychological and Bioethical Analysis in Peru and Mexico - Rios, Liz María Pérez; Bartra, Martín Pinchi (Journal of Ecohumanism, 2024)
This research study examines gender violence as an attack on human integrity and life as a supreme principle, and its relationship within the Peruvian and Mexican legal framework, with the commitments assumed from the perspective of bioethics. To do so, it investigates bioethics, human integrity and the theories that could promote violence directed at women. Gender violence constitutes a global and public health problem; it is, undoubtedly, a transgression of human rights, where life, human integrity and the right to medical care are clearly violated either by action or inaction in the management of rights and established commitments; that is why it is necessary to propose anticipatory, integrative measures, identify, manage and counteract invisibility, normalization, impunity and appreciate the recovery of the human integrity of each woman. These elements could serve as starting points to separate women from violence and carry out all the necessary actions to prevent violence.